HOW DOES THE BUGINESE WOMAN IMAGE IN KETIKA SAATNYA? (POSTCOLONIAL STUDIES AND ISLAMIC PERSPECTIVE) - Rauf, Ramis; Junaid, Syahruni; Ulya, Afriani; Panjaitan, Indra Purnawan; Widhyah Saputri, Dhini Yustia; Lintang Gritantin, Lucia Arter (Elite : English and Literature Journal, 2024)
The anthology of short stories “Ketika Saatnya” is one of the literary works depicting the Buginese woman image written by Darmawati Majid, a Bugis woman. The problem with this article is how the literature illustrates the Buginese woman’s image based on Spivak’s idea of the subaltern and Islamic perspectives on women’s behaviours. This qualitative method, such as postcolonial discourse analysis, involves classifying data according to certain attributes and elements pertinent to the research aims to acquire research outcomes. It categorizes women as a subordinate demographic within society, politics, and geography, subject to the authority of a dominant group, particularly men. Buginese tradition signifies the supremacy of one male faction over another. This research indicates that Bugis women have consistently been placed in subordinate positions. The marginalized minority is portrayed as endeavouring to articulate their viewpoints and attain acknowledgement despite being labelled as “women of underprivileged areas” caught between conventional and Muslim ideologies.